Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 10 - Quadratic Equations - 10.3 - Quadratic Formula - Problem Set 10.3 - Page 453: 45


{$\frac{1-\sqrt {85}}{6},\frac{1+\sqrt {85}}{6}$}

Work Step by Step

Step 1: We write $7=3x^{2}-x$ as $3x^{2}-x-7=0$. Comparing $3x^{2}-x-7=0$ to the standard form of a quadratic equation, $ax^{2}+bx+c=0$, we find: $a=3$, $b=-1$ and $c=-7$ Step 2: The quadratic formula is: $x=\frac{-b \pm \sqrt {b^{2}-4ac}}{2a}$ Step 3: Substituting the values of a, b and c in the formula: $x=\frac{-(-1) \pm \sqrt {(-1)^{2}-4(3)(-7)}}{2(3)}$ Step 4: $x=\frac{1 \pm \sqrt {1+84}}{6}$ Step 5: $x=\frac{1 \pm \sqrt {85}}{6}$ Step 6: $x=\frac{1-\sqrt {85}}{6}$ or $x=\frac{1+\sqrt {85}}{6}$ Step 7: Therefore, the solution set is {$\frac{1-\sqrt {85}}{6},\frac{1+\sqrt {85}}{6}$}.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.